2003
DOI: 10.1002/cne.10872
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular interactions in the mammalian olfactory nerve

Abstract: The small, unmyelinated axons of olfactory sensory neurons project to the olfactory bulb in densely packed fascicles, an arrangement conducive to axo-axonal interactions. We recently demonstrated ephaptic interactions between these axons in the olfactory nerve layer, the layer of the olfactory bulb in which the axon fascicles interweave and rearrange extensively. In the present study, we hypothesized that the axons, which express connexins, may have another mode of communication: gap junctions. Previous transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…3), which produce most of the aqueous nasal secretions that bathe the sensory cilia. Consistent with previous ultrastructural studies (Miragall et al, 1992(Miragall et al, ,1996aBlinder et al, 2003), areas of close membrane apposition identified as gap junctions linked fibroblasts of the lamina propria ( Fig. 2(B)), Bowman's gland cells (Fig.…”
Section: Tem Overview Of Olfactory Mucosa: Olfactory Epithelium and Ssupporting
confidence: 77%
See 2 more Smart Citations
“…3), which produce most of the aqueous nasal secretions that bathe the sensory cilia. Consistent with previous ultrastructural studies (Miragall et al, 1992(Miragall et al, ,1996aBlinder et al, 2003), areas of close membrane apposition identified as gap junctions linked fibroblasts of the lamina propria ( Fig. 2(B)), Bowman's gland cells (Fig.…”
Section: Tem Overview Of Olfactory Mucosa: Olfactory Epithelium and Ssupporting
confidence: 77%
“…Even with high visibility and high detective efficiency of FRIL, no axonal gap junctions were detected, labeled or unlabeled; nor was immunogold labeling above background for any connexin. Similarly, other investigators using conventional freeze fracture did not detect gap junctions between axons or between axons and ensheathing cells (Blinder et al, 2003). Thus, we conclude that gap junctions do not occur (or are extremely rare) between adjacent olfactory axons within the olfactory mucosa, cribriform plate, or olfactory neuron layer of the OB.…”
Section: Olfactory Axons and Their Ensheathing Cellsmentioning
confidence: 66%
See 1 more Smart Citation
“…This has prompted investigations suggesting ephaptic interactions between adjacent axons (Bokil et al 2001;Blinder et al 2003). Thus, tight junctions between OEC processes might serve to conWne interactions between axons.…”
Section: Axonal Growth and The Neurovascular Unitmentioning
confidence: 97%
“…They are primarily observed when the extracellular conductance is reduced (37,280). This condition is fulfilled, for instance, in bundles of unmyelinated axons where the periaxonal space is minimal, as in olfactory nerves (62,68). Ephaptic interactions between axons have also been observed in frog sciatic nerve (288) and in demyelinated spinal axons of dystrophic mice (436).…”
Section: Ephaptic Interactions and Axonal Spike Synchronizationmentioning
confidence: 99%